DESA WISATA HALAL: KONSEP DAN IMPLEMENTASINYA DI INDONESIA - hendri hermawan adinugraha (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
The purpose of this study is to describe the concept and implementation of Halal tourism village. Because the concept of halal now has become a lifestyle for most of Indonesia’s population. This type of research is included in the category of literature research which is the writing of the data and information obtained from reading sources such as from books, research results, journals and other literatures that still have relevance to this research topic. The results showed that the tourism sector has a significant contribution to improving the welfare of an area or country. Halal Tourism Village is an implementation of the embodiment of the nuances of religiosity that is covered in mu’amalah aspect as the embodiment of socio-cultural and socio-economic aspects based on sharia principles. The phenomenon of Halal Tourism Village in Indonesia is now a proof of the flexibility of Islamic law in the practical level of current lifestyle through the integration of the halal and thoyyib values in the tourism sector to support the Islamic regional economy.